(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2014)
The scope of human environmental health laws generally talks about the relationship between human beings and their health environment which amongst others cover enacting laws relating to health and personal safety of an individual. Every individual is a consumer and should be protected. This article focuses on three areas which are food, food handlers and food premises. This research found out that areas relating to food, food mangers and food premises have been legislated with the hope that cleanliness, health and safety of every consumer are guaranteed and at the same time these laws are able to create uniformity in daily way of life of an individual and able to cultivate good practices in their life. The three areas that are legislated are not intended to create problems or hinder economic activities or tie up human freedom in making choices but rather to create clean, healthy and safe environment to consumers and to inculcate awareness about individual’s rights as a consumer besides understanding the meaning of peaceful life. Keywords: consumer, food premises, food contents, food handlers, food legislation